Measurements of CD34+/CD45-dim Stem Cells Predict Healing of Diabetic Neuropathic Wounds - Thom, Stephen R. (Diabetes, 2016)
Management of neuropathic foot ulcers in patients with diabetes (DFUs) has changed little over the past decade, and there is currently no objective method to gauge probability of successful healing. We hypothesized that studies of stem/progenitor cells (SPCs) in the early weeks of standard wound management could predict who will heal within 16 weeks. Blood and debrided wound margins were collected for 8 weeks from 100 patients undergoing weekly evaluations and treatment. SPC number and intracellular content of hypoxia-inducible factors (HIFs) were evaluated by flow cytometry and immunohistochemistry. More SPCs entered the bloodstream in the first 2 weeks of care in patients who healed (n = 37) than in those who did not (n = 63). Logistic regression demonstrated that the number of blood-borne SPCs and the cellular content of HIFs at study entry and the first-week follow-up visit predicted healing. Strong correlations were found among week-to-week assessments of blood-borne SPC HIF factors. We conclude that assays of SPCs during the first weeks of care in patients with DFUs can provide insight into how well wounds will respond and may aid with decisions on the use of adjunctive measures.